CONSUMPTIVISM IN THE GENDER ROLE IN NI NYOMAN SANI’S WORKS OF ART - Suartini, Luh; ., Hardiman (E-Journal of Cultural Studies; Vol 16 No 2 (2023): Volume 16 Number 2 May 2023, 2023)
All this time in visual art in Bali a woman has often been placed as an object per se. Actually, in the visual work of women artists in Bali there is found an ideology that works behind it. This article reveals and describes the gender ideology that works behind the visual representation of Ni Nyoman Sani that is why a descriptive qualitative study is used by using postmodernism theory, visual semiotic theory, gender theory, ideology theory, and psychoanalysis theory to reveal the problem. This article concludes that the gender ideology works behind Ni Nyoman Sani’s work, that is, concerning the consumptivism of the gender role in its use. It is hoped that this discussion can give us a broader and deeper understanding of the gender ideology that works behind Ni Nyoman Sani’s creative process. Keywords : consumptivism, gender role, ni nyoman sani.